2022
DOI: 10.3389/fmicb.2022.1047072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactic acid bacteria, yeast, and their mixture on the chemical composition, fermentation quality, and bacterial community of cellulase-treated Pennisetum sinese silage

Abstract: The present study investigated the effects of Lentilactobacillus buchneri, Saccharomyces cerevisiae, and a mixture of the two on the cellulose degradation and microbial community of cellulase-treated Pennisetum sinese (CTPS) during biological pretreatment. The CTPS was stored without additives (CK) or with L. buchneri (L), yeast (Y, S. cerevisiae), and their mixture (LY) under anaerobic conditions for 60 days. All inoculants enhanced the anaerobic fermentation of CTPS. In relative to L, inoculations with Y and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In the current experiment, the aerobic stability time of the LBC silage was highest, indicating that mixed silage inoculated with lactic acid bacteria and cellulase significantly improved aerobic stability. Among the undesirable microorganisms, yeast is regarded as the promoter of silage spoilage and is closely associated with the increased temperature of silage [41]. We speculate that the improvement in the aerobic stability of the LBC silage was related to the decrease in the yeast count.…”
Section: Discussionmentioning
confidence: 89%
“…In the current experiment, the aerobic stability time of the LBC silage was highest, indicating that mixed silage inoculated with lactic acid bacteria and cellulase significantly improved aerobic stability. Among the undesirable microorganisms, yeast is regarded as the promoter of silage spoilage and is closely associated with the increased temperature of silage [41]. We speculate that the improvement in the aerobic stability of the LBC silage was related to the decrease in the yeast count.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, we believe that the high buffering energy of alfalfa (crude protein up to 18% DM), coupled with the antimicrobial activity of LJH, contributed to the di culty in achieving the desired quality of silage, even with the addition of the LAB. Nevertheless, the addition of LAB was not completely ineffective, as the high acetic acid content in treatment L, and the low lactic acid content in treatment CK, were due to the inoculations of Lactobacillus heterotrophicus and Lentilactobacillus buchneri, which produce acetic acid by breaking down lactic acid (Liao et al, 2022). This variation demonstrates that the inoculation of LAB has an effect on alfalfa that contains antimicrobial ingredients from LJH.…”
Section: Discussionmentioning
confidence: 93%
“…Approximately 20 ml of ltrate for centrifugation (4500 × g, 15 min, 4 ℃). Supernatants were analyzed for lactic, acetic, propionic, and butyric acid by high performance liquid chromatography (Liao et al, 2022). The ammoniacal nitrogen concentration was determined by the method described by Broderick and Kang (1980).…”
Section: Physical and Chemical Analysismentioning
confidence: 99%
“…In the present study, the addition of fibrolytic enzymes resulted in the decrease in pH value of the mixed silage and the increase in LA content. This is due to the fact that cellulase and xylanase could destroy the complex cell wall structure of plants, decompose the structural polysaccharides into monosaccharides or small molecular sugars that can be used by lactic acid bacteria for fermentation, whereby producing a large amount of LA to reduce the pH of silage [ 21 , 22 ]. Similarly, the study of Zhao et al also showed that cellulase could promote LA production and reduce the pH of silage [ 23 ].…”
Section: Discussionmentioning
confidence: 99%